Revised model for radial Basis Function (المجلة العراقية للعلوم الاحصائية, 2008)
In this paper , a revised model for radial basis function has been done with application of sunspot time series. It has been arrived at a revised model for nonlinear time series. The probability characteristics have been explained for such series with chaotic analysis of the simulated data from revised model ,which indicates that the revised model is chaotic and bayesian information criterion ( BIC) Schwarz information criterion (SIC)and the error are better than radial basis function